Intercultural twinning within community organizations in the province of Quebec: A successful practice in reducing prejudices and promoting intergroup contact? - Lacroix, Marie-Ève; Arsenault, Stéphanie; Dioh, Marie-Laure; Lechaume, Aline; Martins Borges, Lucienne; Barré, Marc-Antoine; Gnikpo, Aline (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2024)
To provide immigrants with conditions conducive to their settlement process, community intercultural twinning programs have been deployed in Quebec over the years through different institutions. Those programs are offered to immigrants from all immigration categories and have been acclaimed as tools to foster integration, but also intercultural rapprochement, which is seen as important in the Québécois context because the province continues to experience problems of racism and systemic discrimination. While intercultural twinning programs overseen by education and work institutions have been subject to many studies, intercultural twinning programs in community organizations have received little academic attention, despite presenting differences in participants’ profiles, resources, and sequences. It is important to study this gap because these different types of twinning do not have the same objectives, nor are they based on the same logic. Based on 46 semi-structured interviews, this article addresses one of the effects of participating in a community organization’s intercultural twinning: changes in prejudices among participants. We argue that a positive intercultural twinning experience contributes to reducing prejudices for both newcomers and host society member twins, though a negative intercultural twinning experience can reinforce pre-existing prejudices, especially among participants who had no previous intergroup contact. Previous intercultural experience emerged as a common denominator among host society members interviewed (23/26), but our results show that having previous intercultural experience can also mitigate, in some cases, the reduction of prejudices of participants. Lastly, we have established three categories of factors influencing intercultural twinning relationships: personal, language, and structural. We explain the importance of focusing on all these factors to improve the potential of twinning.